Effects of OmniGen® PRO on ruminal fermentation, stress, and inflammation of Holstein cattle induced with a subacute ruminal acidosis - Jiang, Yun; Chapman, James D.; Humphrey, Brooke; Garcia, Miriam (Frontiers in Animal Science, 2023)
The aim of our study was to examine the effects of an immunomodulatory feed additive (OmniGen ® PRO, Phibro Animal Health, Teaneck, NJ) on ruminal fermentation homeostasis and biomarkers of stress and inflammation in dairy heifers following a subacute ruminal acidosis (SARA). Holstein heifers (n = 32, 8.4 ± 0.3 month old) were blocked to two treatments based on body weight (BW). Treatments were 1) control (CON; n = 16, no additive), and 2) OmniGen ® PRO (OGPRO, n = 16, 10 g/100 kg BW, top-dressed). From d 1 to 69, and d 72 to 77, heifers were fed ad libitum a basal TMR formulated for early lactation. On d 70, the TMR offerings were reduced by 50% based on the intake of the previous 3 d. On d 71, heifers were fed ad libitum a 50/50 mix containing steam-rolled barley and the basal TMR on a DM basis, to induce SARA. Rumen fluid and blood samples were collected on d 66, 71, and 73. Prior to the challenge, DMI, ADG, and feed efficiency were not affected by treatment. Following the challenge, all heifers experienced a 43% decline in DMI. Rumen pH was lower on the challenge day compared to pre-and post-challenge but was unaffected by treatment. Ruminal lactate n was negligible pre-and post-challenge but increased on the challenge day; OGPRO reduced ruminal lactate compared to CON. At all sampling points, rumen total VFA were higher in OGPRO than CON. The challenge caused fluctuation of acetate to propionate ratio in CON, while OGPRO heifers had less variation. Two days post-challenge, OGPRO heifers tended to have lower plasma cortisol, haptoglobin, and non-esterified fatty acids (NEFA) compared to CON. The OGPRO heifers maintained the mean corpuscular hemoglobin concentration (MCHC) and platelet concentration after the challenge, while their levels declined in CON. In this study, supplementing OGPRO to heifers fed an early lactation diet improved rumen fermentation measures prior to the challenge and reduced the negative effects of the challenge on rumen fermentation. In addition, following the challenge, indicators of systemic inflammation tended to be lower in heifers supplemented with OGPRO.